2023
DOI: 10.3389/fevo.2023.1096099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of common palynological extraction treatments on ultraviolet absorbing compounds (UACs) in sub-fossil pollen and spores observed in FTIR spectra

Abstract: IntroductionBiological life, atmospheric circulation and the Earth’s climate may be influenced by UV-B radiation. In plants, Ultraviolet Absorbing Compounds (UACs) are an indicator of UV-B exposure, and the abundance of UACs in pollen and spores of embryophytes is measurable using Fourier Transform Infrared (FTIR) micro-Spectroscopy. However, understanding the influence of common chemical pre-treatments on sub-fossil pollen and spores with a view to UV-B reconstruction still requires investigation.MethodsHere,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…Hence, combined with the results from previous studies reported in the literature (Lyons et al, 1995;Jardine et al, 2015;Wang et al, 2023), our data further strongly support that an alternative method should be applied to clean cuticles, pollen, and spores, for more accurate spectroscopic results.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, combined with the results from previous studies reported in the literature (Lyons et al, 1995;Jardine et al, 2015;Wang et al, 2023), our data further strongly support that an alternative method should be applied to clean cuticles, pollen, and spores, for more accurate spectroscopic results.…”
Section: Discussionsupporting
confidence: 86%